Kebajikan produktif: tahap dan hubungan kesejahteraan, tingkah laku dan pengalaman kewangan dalam kalangan peserta azam tani FAMA - Zurinawaty Mohamad; Nur Saadah Mohamad Aun; Nor Jana Saim (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study of financial well-being has gained considerable attention from researchers from within and outside the country. However, financial well-being study among productive welfare beneficiaries was still too low. This study examined the level and relationship of financial well-being with financial behavior, financial experience and financial knowledge. The research design for this study was quantitative by using survey technique. The study aimed to determine the level of financial well-being among the Fama Azam Tani participants and their relationship to financial behavior, financial experience and financial knowledge. Financial well-being is measured using the Malaysian Financial Well-Being Scale. A total of 300 respondents were involved in this study using simple random sampling techniques. The findings showed that the level of well-being of the participants was at moderate level, the level of financial behavior was at a low level and the level of financial experience was at a high level. In addition, the study also examined the relationship between the variables. The findings showed that there was no relationship between financial behavior with financial well-being. In summary, this study showed that the financial well-being of the Fama Azam Tani participants was still worrying as the group was vulnerable to slipping back into hardcore poor groups.